A Weighted Universality Theorem for L-Functions of Elliptic Curves - Garbaliauskas, Antanas; Garbaliauskienė, Virginija (Jaunųjų mokslininkų darbai, 2018)
In the paper, a short survey on universality results for L-functions of elliptic curves over the field of rational numbers is given and weighted universality theorem is proven. All stated universality theorems are of continuous type. The proof of the universality for L-functions of elliptic curves is based on a limit theorem in the sense of weak convergence of probability measures in the space of analytic functions.
Keywords: elliptic curve; L-function; universality